Study on the compressive behaviour of functional knitted fabrics using elastomeric materials - Fangueiro, Raúl (2010)
This paper describes the research work being done at University of Minho to study the behaviour of weft-knitted fabrics produced with different elastomeric materials to be applied in medical and well-being products. The compressive characteristic of knitted fabrics plays a very important role in several medical situations, such as surgery recovery, pain reduction or leg varicose. An experimental plan has been designed to study the influence of different factors in the compressive behaviour of weft-knitted functional fabrics, including the type of knitted pattern, the linear density of the elastomeric yam, the linear density of the ground yam, fiber cross-section and the type of finishing processes after knitted fabric producing, Different knitted fabrics, produced using a seamless machine, have been tested for cyclic tensile behaviour. The elastic deformation and the permanent deformation of each one has been measured and analysed.